2014
DOI: 10.5539/ies.v7n13p23
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Teachers’ Level of Participation in Online Communities

Abstract: The use of an online learning community is one possible approach to teachers' professional development that can enhance the opportunity for collaboration. Discussions in online learning communities not only allow community members to share resources, ideas and expertise, but also contribute to the fulfilment of teachers' needs in terms of continuous learning and professional development. This paper reports the findings of a study that aimed to explore the factors that influence the way teachers behave in onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…In addition, it is a process of fitting technology to various learning and teaching conditions, whether inside the classroom or outside (Norazrena & Khairul Anuar, 2011;Nur Qistina & Hazman, 2006). Moreover, the integration of ICT in education could increase students' competence based on global needs through skill shaping and increasing knowledge (Storm, 2011), as well as able to enhance students' cooperative learning through community of practice (Khalid et al, 2013(Khalid et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is a process of fitting technology to various learning and teaching conditions, whether inside the classroom or outside (Norazrena & Khairul Anuar, 2011;Nur Qistina & Hazman, 2006). Moreover, the integration of ICT in education could increase students' competence based on global needs through skill shaping and increasing knowledge (Storm, 2011), as well as able to enhance students' cooperative learning through community of practice (Khalid et al, 2013(Khalid et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario was found to be more critical for those who had younger children, i.e. between birth and 12 years old, as at this stage, children need more attention and guidance compared to older children (Khalid et al, 2014). In comparison, for teachers whose children were 18 years and above, the feeling of needing to rush home to the family was not that critical, as their children could take care of themselves.…”
Section: Discussionmentioning
confidence: 94%
“…For examp le, the sharing of teaching practices in the West is carried out publicly and is widely available to colleagues regardless of age and work experience. However, Khalid et al (2014) found that teachers did not fully share their pract ices with the co mmunity because they are afraid that their knowledge and skills are being perceived as condescending. Murugaiah et al 2012similarly found the same issue, which shows that modest cultures exist among teachers.…”
Section: Plc Issuesmentioning
confidence: 99%